2011
DOI: 10.5301/ijao.2011.7748
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Maintenance Hemodialysis with Hemoperfusion: A Safe and Effective Model of Artificial Kidney

Abstract: HD+HP was superior to HD in regularly eliminating middle and large molecule uremic toxins accumulated in the body. These findings suggest a potential role for HD+HP in the treatment to improve the quality of life and survival rate of MHD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 16 publications
3
71
0
Order By: Relevance
“…Clinically, it has been reported that by using HA130 cartridge for patients with end-stage renal disease, there was a better removal of middle uremic toxins compared to the membrane modality, and HP benefits the life quality [32] and nutritional status [41] of long-term dialysis patients. HA230 cartridge has been used for intoxication [42], and might also be used for cancer patients after chemotherapy for the removal of excessive cytostatics in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, it has been reported that by using HA130 cartridge for patients with end-stage renal disease, there was a better removal of middle uremic toxins compared to the membrane modality, and HP benefits the life quality [32] and nutritional status [41] of long-term dialysis patients. HA230 cartridge has been used for intoxication [42], and might also be used for cancer patients after chemotherapy for the removal of excessive cytostatics in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…a late HP conducted HDHP (LHDHP). As the insertion of a HP apparatus into the dialysis circuit during the late course of HD may provoke the status of hypovolemia, EHDHP has been the most widely used mode in most of the dialysis centers, 15,16 to avoid the ultrafiltration-related interdialysis events, such as interdialysis hypotension (IHD).…”
Section: Introductionmentioning
confidence: 99%
“…11 An alternative approach, comprising of sequential hemodialysis and hemoperfusion (HDHP), has been used for about 50 years and proved to be excel over HD in regular elimination of middle-sized molecules and cytokines. [12][13][14][15] In clinical use, HDHP is usually conducted by adding a commercially available hemoperfusion (HP) apparatus into the dialysis circuit in series with a standard hemodialyzer. The HP apparatus generally contains 80-300 g of activated charcoal-coated particles effective for continuous use of approximate two hours.…”
Section: Introductionmentioning
confidence: 99%
“…5 ), which is consistent with other studies [20] . It has also reported that the combined HD + HP treatment can effectively reduce the serum levels of leptin, hsCRP, β2-MG, IL-6, iPTH and TNF-α [21,22] . However, our study found that the combined HD + HP treatment did not alter the levels of hsCRP and IL-6, although the serum level of TNF-α is significantly low.…”
Section: Discussionmentioning
confidence: 99%